POLA BERTANYA SISWA SEKOLAH DASAR MELALUI MODEL SITUATION-BASED LEARNING PADA MATERI PERUBAHAN WUJUD BENDA - Silaban, Pitria; Jayadinata, Asep Kurnia; Atun, Isrok (Jurnal Pena Ilmiah, 2019)
AbstractThe ability to ask and to get students in learning needs to develop ways of thinking students in solving problems. In the process of learning, deserts have an important role in seeing the difficulties of learning in students. Learning difficulties can be seen through students who are reluctant to ask. This study aims to find out the difficulties of the students in asking, knowing the types of questions raised by students, knowing the competencies of students in basic learning in a question and knowing the tendency of elementary school students in asking questions between oral and written. The research method used is Descriptive Research Qualitatively in two meetings by applying the Situation-Based Learning model. Based on the identification of student difficulties in asking, it can be concluded that the difficulty of asking students is categorized as low, the types of questions raised by students are the types of knowledge questions and have a low level of questions. The results of the students' courage were 73.5% so that they were classified into the level of courage being at intervals (51% -75%). Students have a tendency to ask verbally, students are more likely to ask peers than to teachers because assuming teachers always give a serious impression, students are also very interested in accessing the internet because they think everything that is asked can be found easily on the internet.